Lipid-Based Nanocarriers for Neurological Disorders: A Review of the State-of-the-Art and Therapeutic Success to Date - Bwalya Angel Witika; Madan Sai Poka; Patrick Hulisani Demana; Scott Kaba Matafwali; Siyabonga Melamane; Sandile Maswazi Malungelo Khamanga; Pedzisai Anotida Makoni (MDPI AG, 2022)
Neurodegenerative disorders including Alzheimer's, Parkinson's, and dementia are chronic and advanced diseases that are associated with loss of neurons and other related pathologies. Furthermore, these disorders involve structural and functional defections of the blood-brain barrier (BBB). Consequently, advances in medicines and therapeutics have led to a better appreciation of various pathways associated with the development of neurodegenerative disorders, thus focusing on drug discovery and research for targeted drug therapy to the central nervous system (CNS). Although the BBB functions as a shield to prevent toxins in the blood from reaching the brain, drug delivery to the CNS is hindered by its presence. Owing to this, various formulation approaches, including the use of lipid-based nanocarriers, have been proposed to address shortcomings related to BBB permeation in CNS-targeted therapy, thus showing the potential of these carriers for translation into clinical use. Nevertheless, to date, none of these nanocarriers has been granted market authorization following the successful completion of all stages of clinical trials. While the aforementioned benefits of using lipid-based carriers underscores the need to fast-track their translational development into clinical practice, technological advances need to be initiated to achieve appropriate capacity for scale-up and the production of affordable dosage forms.